"The Uniform's in the Way": Navigating the Tension Between Security and Therapeutic Roles in a Rehabilitation-Focused Prison in Norway. (April 2023) - Kilmer, Ashley; Abdel-Salam, Sami; Silver, Ian A.
The Norwegian Correctional Service ascribes to both a humane and rehabilitative approach to incarceration which includes the use of dynamic security practices, emphasizing relationship-building and communication between officers and incarcerated individuals. In addition, officers are expected to actively participate in the rehabilitative process. Despite Norway's low rates of prison-based violence, there remain questions about officers' ability to implement dynamic security and contribute to therapeutic goals. The current study explores perspectives about dynamic security and officer relationships using a questionnaire ( n = 81) and semi-structured interview ( n = 47) data from individuals incarcerated at Halden Prison in Norway. Findings indicate that officers have generally attained authoritative legitimacy through dynamic security, but their participation in the rehabilitative process is met with resistance stemming from prison culture expectations of officers' role in enacting State punishment. Results from this study provide meaningful insights into the role of dynamic security implementation and the contributions of correctional officers to the rehabilitative process.